Development and Evaluation of an ESP32-based Temperature and Humidity Control Unit for Textile Storage - Dedy Harianto; Hamdan S. Bintang; Agus Ardiyanto; Vallen Laurinda Defrina Widyawan (International Journal of Engineering Continuity, 2025)
Monitoring temperature and humidity in textile storage warehouses is vital for maintaining product quality and ensuring optimal conditions. This study focuses on developing a temperature and humidity control unit using an ESP32 microcontroller, evaluating its performance through black-box testing. The ESP32-based system offers a scalable and energy-efficient solution for climate control, delivering precise environmental monitoring through integrated Wi-Fi and Bluetooth for affordable connectivity. Its advanced real-time data processing capabilities and compatibility with multiple sensors make it highly suitable for cost-effective, large-scale implementations in textile storage environments. The experimental approach involves controlling temperature and humidity as independent variables, while ensuring optimal storage as the dependent variable. The DHT21 sensor, ESP32 microcontroller, and relay are used as control variables. Software was developed in the Arduino IDE to manage temperature and humidity, and after validation, the program was uploaded to the ESP32 for black box testing. Results confirmed that the system effectively regulates these conditions, crucial for preserving textiles. The ESP32 efficiently serves as the control unit, and testing validated its ability to maintain desired limits. Future improvements could include wireless access for remote monitoring, enhancing flexibility and operational efficiency in environmental control for textile storage.